SAT0163 Defective autophagy in T lymphocytes from patients with systemic lupus erythematosus: Potential role of anti-lymphocyte autoantibodies. (23rd January 2014) - Alessandri, C.; Pierdominici, M.; Conti, F.; Truglia, S.; Barbati, C.; Pendolino, M.; Vacirca, D.; Piscopo, P.; Maselli, A.; Colasanti, T.; Perl, A.; Ortona, E.; et al.
Abstract : Background: Autophagy, the cytoprotection mechanism that takes place in cells under metabolic impairment, has been implicated in the pathogenesis of autoimmune diseases (1-5). Evidence also supports a role for sera obtained from patients with systemic lupus erythematosus (SLE) in inducing autophagy, thus suggesting the hypothesis that autophagy could play a pathogenetic role in autoimmunity. Objectives: We investigated the autophagic behaviour of peripheral T lymphocytes obtained from patients with SLE and healthy donors. We also tested the hypothesis that humoral autoimmune factors may contribute to the dysregulation of lymphocyte homeostasis in SLE via a pathway involving autophagy modulation. Methods: Thirty-four consecutive patients with SLE (32 women, 2 men) and an equal number of age-and sex-matched healthy donors were enrolled in the study. Current SLE disease activity was measured using the SLE Disease Activity Index (SLEDAI). Disease modyfing antirheumatic drugs were discontinued at least 24 hours before venipuncture. The experimental methods included combined cellular and molecular approaches (cell culture techniques, flow cytometry, Western blot, RT-PCR). Results: In order to reveal differences in the autophagy level between T cells from SLE patients and healthy donors, ex vivo analysis of these cells for the presence of the autophagosomal marker microtubule-associated protein-1 light chain 3 (LC3)-II was performed by Western blot. A great inter-individual variability for LC3-II levels was present both in SLE patients and in healthy donors. However, there were no significant differences in the quantity of LC3-II in SLE compared with normal T cells. Further experiments were performed in vitro challenging lymphocytes with sera collected from SLE patients. We found that SLE sera increased autophagy in T lymphocytes from healthy donors via a mechanism involving anti-lymphocyte antibodies, while they were ineffective in inducing autophagy in T lymphocytes from SLE patients. Accordingly, genes negatively regulating autophagy were upregulated in lymphocytes from SLE patients. Conclusions: Our data clearly suggest that a defective autophagy can occur in T cells from SLE patients. This could open new perspectives in molecularly targeted therapeutic strategies aimed at the modulation of the T cells autophagic propensity in SLE. References: Levine, B., and Kroemer, G. (2008) Cell 132, 27-42 Harley, J.B. et al. (2008) Nat Genet 40, 204-210 Perl, A. (2010) Autoimmunity 43, 32-47 Zhou, X.J. et al. (2011) Ann Rheum Dis 70, 1330-1337 Towns, R. et al. (2005) Autophagy 1, 163-170 Disclosure of Interest: None Declared